Simultaneous measurements of particle number size distributions at ground level and 260 m on a meteorological tower in urban Beijing, China - W. Du; W. Du; J. Zhao; J. Zhao; Y. Wang; Y. Zhang; Y. Zhang; Q. Wang; W. Xu; W. Xu; C. Chen; T. Han; et al. (Atmospheric Chemistry and Physics, 2017)
Despite extensive studies into the characterization of particle number size distributions at ground level, real-time measurements above the urban canopy in the megacity of Beijing have never been performed to date. Here we conducted the first simultaneous measurements of size-resolved particle number concentrations at ground level and 260 m in urban Beijing from 22 August to 30 September. Our results showed overall similar temporal variations in number size distributions between ground level and 260 m, yet periods with significant differences were also observed. Particularly, accumulation-mode particles were highly correlated (r2 = 0. 85) at the two heights, while Aitken-mode particles presented more differences. Detailed analysis suggests that the vertical differences in number concentrations strongly depended on particle size, and particles with a mobility diameter between 100 and 200 nm generally showed higher concentrations at higher altitudes. Particle growth rates and condensation sinks were also calculated, which were 3.2 and 3.6 nm h−1, and 2.8  ×  10−2 and 2.9  ×  10−2 s−1, at ground level and 260 m, respectively. By linking particle growth with aerosol composition, we found that organics appeared to play an important role in the early stage of the growth (09:00–12:00 LT) while sulfate was also important during the later period. Positive matrix factorization of size-resolved number concentrations identified three common sources at ground level and 260 m, including a factor associated with new particle formation and growth events (NPEs), and two secondary factors that represent photochemical processing and regional transport. Cooking emission was found to have a large contribution to small particles and showed much higher concentration at ground level than 260 m in the evening. These results imply that investigation of NPEs at ground level in megacities needs to consider the influences of local cooking emissions. The impacts of regional emission controls on particle number concentrations were also illustrated. Our results showed that regional emission controls have a dominant impact on accumulation-mode particles by decreasing gas precursors and particulate matter loadings, and hence suppressing particle growth. In contrast, the influences on Aitken particles were much smaller due to the enhanced new particle formation (NPF) events.